The Changing Status of Women in Politics and Society: Ghana - May, Madison (My University, 2016)
Since becoming the first African nation to gain independence in 1957, Ghana has been a trendsetter in many political endeavors. With an established presidential democracy, a diverse ethnic population of over 27 million, and one of the strongest economies in continental Africa, Ghana is a leader in development. Even though it has been able to maintain free and fair elections and has established many government programs to promote civic participation and engagement, Ghana is still lacking behind its Western counterparts in gender equality in the workforce and in government. As noted by historians Jane Parpart and Kathleen Staudt (1998, p. 98): “Patriarchal traditions are so ingrained in the fabric of society [that] women’s struggle for emancipation is replete with contradictions, ambivalence, and silence.” Taking certain steps to increase women’s presence and participation in government would yield enormous benefits for the nation as a whole, including social, economical, and environmental returns. To support this theory, I will draw upon my own experience working for the National Commission for Civic Engagement in Gomoa Benso, Ghana.